2018
DOI: 10.1371/journal.pone.0205802
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy evaluation of "Dat-e Adolescence": A dating violence prevention program in Spain

Abstract: This study presents the first evaluation of Dat-e Adolescence, a dating violence prevention program aimed at adolescents in Spain. A cluster randomized control trial was used involving two groups (a control group and experimental group) and two waves (pre-test and post-test six months apart). 1,764 students from across seven state high schools in Andalucía (southern Spain) participated in the study (856 in the control group and 908 in the experimental group); 52.3% were boys (n = 918), with ages ranging from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 59 publications
1
55
0
8
Order By: Relevance
“…This program also intervenes in romantic relationship quality, yielding positive results for support and future expectations. Within this framework, Dat-e Adolescence [37] has emerged as a response to the need for developing programs with high methodological quality and inspired by an evidence-based approach in the area of dating violence prevention in Spain. The aim of the present study was to examine the efficacy of the Dat-e Adolescence program (First Edition) in relation to reducing dating violence and bullying at follow-up measurement, that is, in the longer term as compared to the intervention implementation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This program also intervenes in romantic relationship quality, yielding positive results for support and future expectations. Within this framework, Dat-e Adolescence [37] has emerged as a response to the need for developing programs with high methodological quality and inspired by an evidence-based approach in the area of dating violence prevention in Spain. The aim of the present study was to examine the efficacy of the Dat-e Adolescence program (First Edition) in relation to reducing dating violence and bullying at follow-up measurement, that is, in the longer term as compared to the intervention implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of Dat-e Adolescence has been assessed over two large RCT waves [37]. The program significantly modified beliefs towards violence, specifically on myths about romantic love (Cohen’s d from −0.56 to −0.94); enhanced self-esteem ( d = −0.15); and emotion regulation ( d = −0.19) among participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review carried out with 113 studies of dating violence prevalence perpetrated and received, among adolescents and young adults (Rubio-Garay, López-González, Carrasco & Amor, 2017) found that between 8.5% and 95.5% of the participants had been victims of psychological violence, between 0.4% and 57.3% of physical violence and between 0.1% and 64.6% of sexual violence, while between 4.2% and 97% of participants had perpetrated psychological violence, between 3.8% and 41.9% physical violence and between 1.2% and 58.8% sexual violence. In addition, the results of these studies show that dating violence occurs bi-directionally in a significant number of cases (Alegría & Rodríguez, 2015, Rubio-Garay et al, 2017, Sánchez-Jiménez et al, 2018.…”
mentioning
confidence: 99%
“…The existing efforts have focused on prevention, but in this field the studies indicate that the developed programs have, in general, a positive impact on the knowledge of this phenomenon, with a decrease in the attitudes and beliefs that promote violence, but they do not report the impact of these programs on the behavior of individuals or it is less (Leen et al, 2013;. Sánchez-Jiménez et al (2018), for example, evaluated a multicomponent prevention program through a controlled clinical trial in which 1764 Spanish students from 12 to 19 years old participated, finding that this program had increased knowledge on the subject and had diminished attitudes and beliefs about romantic love that promoted this type of violence, but had not had a positive impact on the aggressive behavior of the experimental group participants or on victimization. A systematic review by Leen et al (2013), on prevention and intervention programs of dating violence directed at adolescents, published between 2000 and 2011, found a total of nine studies describing primary and secondary prevention programs implemented in the United States or Canada, most of them which had been designed for educational environments, in order to develop skills for the improvement of couple relationships with different pedagogical approaches, but none corresponded with treatment programs aimed at victims or perpetrators of this type of violence.…”
mentioning
confidence: 99%